(untitled) (Jurnal Bahasa Lingua Scientia, 2023)
English literacy has been taught to students as a foreign language due to globalization. Learning English reading literacy begins at a young age and starts by learning words. Phonemic awareness aids the students in learning words in-depth and acts as the platform to identify a reading failure. The current research aims to find whether phonemic awareness and reading comprehension are related. The data for measuring phonemic awareness and reading comprehension was collected using a test and analyzed using IBM SPSS 25.0. The current study revealed that phonemic awareness is related positively to reading comprehension. Moreover, the students are revealed to understand learned words well. This research brings significance to teaching phonemes to young children to aid them in learning reading English. For future research, phonemic awareness should be paid attention to in learning reading comprehension by giving the students various English word reading exercises